Pylephlebitis With Concomitant Fusobacterium Bacteremia: Lemierre's Syndrome Variant of the Gut - Mackenzie R. Barker; Mahmoud Khreis (Annals of Internal Medicine: Clinical Cases)
Pylephlebitis is a rare complication of intra-abdominal infections, and Fusobacterium, traditionally associated with thrombophlebitis of the internal jugular vein, is an extremely rare causative organism. This infection is associated with high morbidity and mortality, and there is still some controversy about management. Here, we report a patient who presented with pylephlebitis and Fusobacterium bacteremia and responded well to a short course of intravenous antibiotics, finished therapy in the outpatient setting, and made a full recovery. We also review relevant literature on treatment strategies including antibiotics, anticoagulation, and screening endoscopy.